2012
DOI: 10.2459/jcm.0b013e3283542031
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of nicorandil on rat myocardial ischemia-reperfusion

Abstract: A suitable level of nicorandil has a protective effect on rats' myocardial ischemia-reperfusion injury, and is mainly based on the opening of the mitochondrial KATP channel and the lowing of Ca overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Nishikawa et al (25) demonstrated that nicorandil inhibited hypoxia-induced Bcl-2 downregulation and Bax upregulation in mitochondria, and thus protected cardiomyocytes. Furthermore, Wang et al (26) also found that, when administered before/during ischemia or at the onset of reperfusion, nicorandil increased Bcl-2 expression and reduced Bax expression in normal Sprague-Dawley rats. In agreement with these observations, the present study demonstrated that respective nicorandil preconditioning and postconditioning significantly upregulated the expression of Bcl-2 and downregulated the expression of Bax in hypercholesterolemic hearts, suggesting that the cardioprotective effects of nicorandil may be mediated by regulation of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nishikawa et al (25) demonstrated that nicorandil inhibited hypoxia-induced Bcl-2 downregulation and Bax upregulation in mitochondria, and thus protected cardiomyocytes. Furthermore, Wang et al (26) also found that, when administered before/during ischemia or at the onset of reperfusion, nicorandil increased Bcl-2 expression and reduced Bax expression in normal Sprague-Dawley rats. In agreement with these observations, the present study demonstrated that respective nicorandil preconditioning and postconditioning significantly upregulated the expression of Bcl-2 and downregulated the expression of Bax in hypercholesterolemic hearts, suggesting that the cardioprotective effects of nicorandil may be mediated by regulation of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 97%
“…Fig. 4 26.18±4.82%) respectively, as compared with untreated samples. Together, these results suggested that nicorandil preconditioning and postconditioning may protect hypercholesterolemic hearts against I/R-induced infarction and apoptosis, which are both stimulated by the opening of mitoKATP channels and a NO/sGC dependent mechanism.…”
Section: Effects Of a High-cholesterol Diet On Serum Lipid Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakai (17) reported that nicorandil exerted blood pressure-lowing effects, which subsequently reduced cardiac hypertrophy in animals (17). Regardless of the precise mechanism of nicorandil in cardiovascular diseases, our previous study also demonstrated the protective effects of nicorandil against myocardial ischemia-reperfusion injury, which were due in part to the opening of mitoK ATP channels (13). It was found in the present study that long-term oral administration of nicorandil is beneficial for the reduction of cardiac hypertrophy and modulation of myocardial Cx43 in Iso-induced rat models of cardiac hypertrophy.…”
Section: A B C D Ementioning
confidence: 87%
“…Activation of the K ATP channel inhibits GJ permeability and subsequently attenuates arrhythmias in the acute ischemic myocardium (10). Numerous studies have demonstrated the protective effect of Cx43 against ischemic injury by the administration of a K ATP channel agonist (11)(12)(13). However, no favorable effects have been shown in transgenic animals with a Cx43 deficiency (10).…”
Section: Introductionmentioning
confidence: 99%